Exploring the catalytic potential of nitrilase from Alkalophilic Rhodococcus Pyridinivorans NIT-36 for nitrile degradation (Funded work) - AMIT SETH,; RUCHIKA SHARMA,; MAMTA SHARMA,; CHANDRIKA ATTRI, (International Journal of Pharma and Bio Sciences, 2017)
An alkalophilic nitrilase-producing strain capable of transforming both aliphatic and aromatic nitriles was isolated from hot-water springs of Tattapani, Himachal Pradesh. On the basis of 16S rDNA gene sequencing this isolate was designated as Rhodococcus pyridinivorans NIT-36. The optimization of reaction parameters was performed by using benzonitrile and acrylonitrile as substrates and maximum conversion to respective acids was observed in 0.1M sodium bicarbonate buffer having alkaline pH 10. Whole cell immobilization of R. pyridinivorans NIT-36 was carried out in polyacrylamide, sodium alginate and agar as matrix. Highest activity and thermostability was observed for agar immobilized cells and they retained 70% activity even after 5 h.Optimization of reaction conditionsby using response surface methodology led to 3.8 and 1.5 fold increase in nitrilase activity of free and immobilized cells respectively. Further, scale-up studiesresulted in production of 53 g/L of benzoic acid for free cells and and 10g/L for agar immobilized cells. Since R. pyridinivorans is capable of degrading nitriles under wide pH range especially in highly alkaline conditions, it is a suitable candidate for industrial applications.